Tantangan Orang Tua dalam Mendidik Anak yang Kecanduan Gadget - Dira Zahara Fitri; Viny Syahputri; Faisal Akbar; Arlina Sirait (Universitas 45 Surabaya, 2024)
This research aims to find out and overcome the challenges faced by parents of children who are addicted to gadgets. This type of research is descriptive research with qualitative research methods. The instruments used were interviews and observations of parents and children who were addicted to gadgets. The results of this research show several challenges faced by parents in dealing with children who are addicted to gadgets and there are several ways parents use to deal with children who are addicted to gadgets.